2018
DOI: 10.1111/fare.12308
|View full text |Cite
|
Sign up to set email alerts
|

Parental Depression and Cooperative Coparenting: A Longitudinal and Dyadic Approach

Abstract: Policy makers and family practitioners who are invested in building healthy families may find it valuable to screen for and treat mental illness in the context of creating programs to increase cooperative coparenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 76 publications
6
37
2
7
Order By: Relevance
“…Second, the differences between mothers and fathers in the timing of the associations may reflect gendered processes in heterosexual relationships. For example, mothers tend to be more involved with children at younger ages, whereas fathers tend to increase their parental involvement when children become older (Williams, ). We note that these interpretations are largely speculative, and more research is needed on the longitudinal and bidirectional association between parenting stress and relationship quality using the RI‐CLPM.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the differences between mothers and fathers in the timing of the associations may reflect gendered processes in heterosexual relationships. For example, mothers tend to be more involved with children at younger ages, whereas fathers tend to increase their parental involvement when children become older (Williams, ). We note that these interpretations are largely speculative, and more research is needed on the longitudinal and bidirectional association between parenting stress and relationship quality using the RI‐CLPM.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that increased father involvement in parental caregiving both enhances (Cowan, Cowan, Pruett, & Pruett, 2018;Pruett et al, 2017) and is enhanced by (Murphy et al, 2017) positive co-parenting, with consequent benefits for both the child's development and the relationship between the parents (Casey et al, 2017;Cowan, Cowan, & Mehta, 2009;Cowan et al, 2018;Pruett et al, 2017). Notably, influences between co-parents are strong but complex (e.g., Cabrera, Fagan, Wigh, & Schadler, 2011;Psouni, Agebjörn, & Linder, 2017;Williams, 2018), involving interactions of parents' beliefs, social values, desires and expectations (Feinberg, 2003). For instance, co-parents may be aligned in thought processes regarding caregiving and behave similarly in attachment-related situations (Howes & Spieker, 2008), but it has also been suggested that, rather, the mother's feelings and attitudes have an impact on features of the father's relationship to the child, for example, in terms of frequency and context (Allen & Hawkins, 1999;Murphy et al, 2017).…”
Section: Co-parent Influencesmentioning
confidence: 99%
“…Além de trazer consequências negativas à mãe, a depressão afeta as relações entre todos os membros da família (Frizzo, Prado, Linares, & Piccinini, 2011a;Silva, Pizeta, & Loureiro, 2016;Williams, 2018). Isso ocorre tanto pela seriedade da situação clínica, como pelo fato de que aquilo que acontece a um dos membros da família tende a impactar todos os demais, pois eles interagem e se influenciam mutuamente, como destacado pela teoria sistêmica (McDaniel, 2016;Minuchin, 1982).…”
Section: Introductionunclassified
“…Assim, também há indicativos de desdobramentos negativos para as relações triádicas, no sentido de que a depressão pode fragilizar a coparentalidade (Don et al, 2013;Favez, Tissot, Frascarolo, Stiefel, & Despland, 2016;Pinto, 2014;Williams, 2018). O estudo de Favez, Tissot, Frascarolo, Stiefel e Despland, (2016), com 69 tríades mãe-pai-bebê suíços, evidenciou que quanto mais depressão, mais conflito e menos apoio parental.…”
Section: Introductionunclassified
See 1 more Smart Citation